Problem Based Learning (PBL) Learning Model to Improve Civic Education (PKn) Learning Outcomes of Elementary School Students - Ilham, Muhammad Afrian (International Journal of Students Education, 2025)
The main problem in this study is the learning model that tends to make students bored which affects low student learning outcomes. One way to improve student learning outcomes is by using the Problem Based Learning learning model. The problem-based learning model is one of the innovative learning models that can provide active learning conditions. In the world of education, improving students’ critical thinking skills is needed to provide a learning process that influences student knowledge. This applies to the PKn learning process in elementary schools which has an influence on improving students’ critical thinking skills. This study aims to determine the application of improving the Problem Based Learning (PBL) learning model to the PKn learning outcomes of elementary school students. The method used in this study is a literature review with the method of collecting library data, and managing studies sourced from books or journals that have been previously analyzed. The results of the study found that the level of critical thinking of students increased after the application of the problem based learning model. This is evidenced by student activity, diverse discussion results, and more interaction between students. Students have new experiences after the application of problem based learning, especially in solving problems in the real world.